Notationskunde: Schrift und komposition 900-1900 - Schmid, Manfred Hermann 1947- (Kassel Bärenreiter Studiebücher Musik, 2012)
Musical notation from past eras often seems as decorative as an exotic plant, but at the same time it is also very enigmatic. Those who learn to understand it, however, can not only make their own transcriptions and make music from them, but also gain an insight into the entire musical thinking of an era.In Manfred Hermann Schmid's new, practical study of notation, both aspects go hand in hand: the explanation of the writing and its relationship to the composition of the respective period. The author presents the ‘classical field’ of notation, the theory of rhythm from 1200 to 1600 (Notre Dame, Ars nova, white mensural notation), in a compact manner and focussed on the essential lines. In addition, he gives a step-by-step introduction to the theory of ancient music and the medieval scripts up to the neumatic notation of Gregorian chant. He also explains score arrangements from Monteverdi to Wagner and various tablatures and reflects on the limits of writing.With its broad horizon, this fluently written book takes the reader on a journey of discovery. As if in passing, you learn why the highest notes on a piano are on the right and the semitones on a harp are marked in yellow and red, that Gregorian chant was probably sung much more ‘oriental’ than modern writing can reproduce, and how notation influenced composition in general. A sideways glance at ethnomusicology also brings astonishing insights. (Translated with DeepL.com)
Keywords: Music history; Composing; Notation